A Strategies of Success Virtual Mobility for Technical Students - Isa, K, Isa, K; Wan Muda W.H.N, Wan Muda W.H.N; Halim, F, Halim, F; Ismail, N, Ismail, N (RES MILITARIS, 2023)
Student mobility program have risen to the top of local universities' worldwide priorities. In addition to giving university students the chance to learn about different cultures, this programme helps expose them to various study strategies. Mobility programmes should adopt a new strategy in the age of Revolution Industry 4.0 and use technology as the vehicle for implementation. This study aims to determine whether virtual mobility programmes are appropriate for implementation, the level of students' knowledge regarding virtual mobility implementation, the reasons why students joined virtual mobility programmes, and the kinds of media that students anticipated using when participating in virtual mobility. Quantitative method was used with survey questionnaire to collect the data. A total of 304 students of Malaysian Technical Higher Institution were involved as a sample in this study also descriptive and inferential analysis were employed to this study. The findings showed that virtual mobility can be seen as an alternative for conventional mobility and it still has an impact on students’ soft skills. Besides, the data showed that the level of students’ knowledge towards the implementation of virtual mobility is moderate and majority of the respondents decided to join the virtual mobility program because they could develop their information technology skills. Meanwhile, most of the respondents expected to use internet as a main medium to join the virtual mobility program.